Implementasi Pelibatan Masyarakat dalam Peningkatan Kualitas Pendidikan Berdasarkan Instrumen Akreditasi Satuan Pendidikan (IASP) Tahun 2020 (Studi Deskriptif: MA Negeri 2 Kota Bandung) - Aisyah, IA Siti; Nugraha, Mulyawan Safwandy (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2024)
Abstract Educational institutions are the birthplace of the nation's intellectual generations, in maintaining educational institutions, of course, meeting the needs and expectations of the community towards education must be considered, thus the implementation of community involvement or school committees is needed. Where the purpose of this study is to find out how the implementation of community involvement or committees can be implemented in reality. The research method in this study uses a descriptive method with a qualitative approach. The results of the findings obtained by researchers on community involvement or school committees have been well implemented in MA Negeri 2 Bandung City by involving the committee in three ways, including in program planning by holding a meeting every year and inviting the committee to attend. Second, the involvement of the committee in the implementation of the program, this involvement can be in the form of attending the activities directly or providing support in the form of facilities, finance or thoughts. Third, involvement in program control or evaluation by providing direction, input, or evaluating funds that have been used in program implementation.